A new method for high resolution well-control processing of post-stack seismic data - Dakui Wu; Zongwei Wu; Yijia Wu (Natural Gas Industry B, 2020)
Increasing the resolution of seismic data has long been a major topic in seismic exploration. Due to the effect of high-frequency noises, traditional methods could only improve the resolution limitedly. To end this, this paper newly proposed a high-resolution seismic data processing method based on well–seismic combination after summarizing the research status on high resolution. Synthetic record and seismogram are similar in effective signals but dissimilar in noises. Their effective signals are regular and noises are irregular. And they are similar in adjacent frequency. Based on these “three-regularity” characteristics, the relationship between synthetic record and seismogram was established using the neural network algorithm. Then, the corresponding extrapolation algorithm was proposed based on the self-adaptive geological and geophysical variation of multi-layer network structure. And a model was established by virtue of this method and the theoretical simulation was carried out. In addition, it was tested from the aspects of frequency component and amplitude energy recovery, phase correction, regularity elimination and stochastic noise. And the following research results were obtained. First, this new method can extract high-frequency information as much as possible and remain middle and low-frequency effective information while eliminating the noises. Second, in this method, the idea of traditional methods to denoise first and then expand frequency is changed completely and the limitation of traditional methods is broken. It establishes the idea of expanding frequency and denoising simultaneously and increases the resolution to the uttermost. Third, this new method has been applied to a variety of reservoir descriptions and the high-resolution processing results have been improved significantly in precision and accuracy.